2014
DOI: 10.1097/mpg.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Hepatitis With Autoimmune Hemolytic Anemia in Children

Abstract: We propose Rtx as the treatment of choice for severe GCH with AIHA in the early stages of the disease, provided steroids and azathioprine are ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
2
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 17 publications
1
21
2
2
Order By: Relevance
“…suggested that systemic B‐lymphocyte autoimmunity plays a central role in the pathologic mechanism . In contrast to autoimmune hepatitis, however, autoantibodies associated with liver disease, such as ANA, anti‐smooth muscle antibody, anti‐mitochondrial antibody, and anti‐liver–kidney microsomal antibody, were found in a few cases . In the present case, ANA and anti‐smooth muscle antibodies were found at initial diagnosis.…”
Section: Discussioncontrasting
confidence: 51%
“…suggested that systemic B‐lymphocyte autoimmunity plays a central role in the pathologic mechanism . In contrast to autoimmune hepatitis, however, autoantibodies associated with liver disease, such as ANA, anti‐smooth muscle antibody, anti‐mitochondrial antibody, and anti‐liver–kidney microsomal antibody, were found in a few cases . In the present case, ANA and anti‐smooth muscle antibodies were found at initial diagnosis.…”
Section: Discussioncontrasting
confidence: 51%
“…Rituximab (RTX), which is believed, in particular, to deplete CD20-positive autoreactive plasma cells sparing protective antimicrobial plasma cells [18], was recently shown to induce and maintain remission in a small series of patients with severe liver disease [9,10]. Moreover, RTX has been also shown to act as a steroid-sparing drug, permitting patients to be weaned off corticosteroid therapy, particularly in case of an early treatment [10].…”
Section: Discussionmentioning
confidence: 98%
“…A recent study demonstrated a diffuse C5b-9 complex deposition on the membrane of giant hepatocytes, suggesting that liver cell injury might be autoantibodydriven and complement-mediated, as in the case of the associated Coombs-positive hemolytic anaemia [8]. Moreover prolonged remission has been recently reported using B cell depletion immunotherapy with chimeric anti-CD20 monoclonal antibody (rituximab) [2,9,10].…”
mentioning
confidence: 96%
See 2 more Smart Citations